2010
DOI: 10.1063/1.3471446
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond symmetrization and superconducting phase of HBr and HCl under high pressure: An ab initio study

Abstract: Ab initio calculations are performed to probe the hydrogen bonding, structural, and superconducting behaviors of HBr and HCl under high pressure. The calculated results show that the hydrogen bond symmetrization (Cmc2(1)-->Cmcm transition) of HBr and HCl occurs at 25 and 40 GPa, respectively, which can be attributed to the symmetry stretching A(1) mode softening. After hydrogen bond symmetrization, a pressure-induced soft transverse acoustic phonon mode of Cmcm phase is identified and a unique metallic phase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 46 publications
1
38
3
Order By: Relevance
“…H 2 I and H 4 I are both suggested to be superconducting at pressures of 100 GPa but are unlikely to be stable with respect to decomposition to their constituent elements at such conditions [8,9]. This may also hold true for the superconducting phases of HCl and HBr predicted at pressures of 280 GPa and 160 GPa, respectively [33]. At pressures up to 60 GPa and at temperatures of 80 K and 300 K, we observed no further reaction between H 2 and I 2 , suggesting that much higher pressures and most probably high temperature to overcome the kinetic barrier would be required to promote formation of any the theoretically predicted H 2 -I 2 compounds [8,9].…”
Section: Discussionmentioning
confidence: 96%
“…H 2 I and H 4 I are both suggested to be superconducting at pressures of 100 GPa but are unlikely to be stable with respect to decomposition to their constituent elements at such conditions [8,9]. This may also hold true for the superconducting phases of HCl and HBr predicted at pressures of 280 GPa and 160 GPa, respectively [33]. At pressures up to 60 GPa and at temperatures of 80 K and 300 K, we observed no further reaction between H 2 and I 2 , suggesting that much higher pressures and most probably high temperature to overcome the kinetic barrier would be required to promote formation of any the theoretically predicted H 2 -I 2 compounds [8,9].…”
Section: Discussionmentioning
confidence: 96%
“…Hydrogen-bond symmetrization has been found in hydrogen-bonded molecular compounds such as H 2 O, NH 3 , HF, HCl and HBr Duan et al, 2010;Zhang et al, 2010). Hydrogen bonds are typically weaker than covalent, ionic and metallic bonds, but stronger than van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
“…ular interactions, such as hydrogen bonds (A-H · · · B) and halogen bond (halogen · · · halogen). [20][21][22][23][24][25] It is demonstrated that these interactions play an important role in the formation of crystal structures, crystal packing, protein folding, and biological materials. 23,25 Several studies have reported the significant effect of pressure on enhancing molecular aggregates and controlling the strength of C-H · · · X (X = F, Cl, Br, and I) and halogen · · · halogen interactions.…”
Section: Introductionmentioning
confidence: 99%